Absence of Uptake and Prion-Like Spreading of Alpha-Synuclein and Tau After Intravitreal Injection of Preformed Fibrils - Veys, Lien; Van houcke, Jessie; Aerts, Jeroen; Van Pottelberge, Sophie; Mahieu, Michel; Coens, Audrey; Melki, Ronald; Moechars, Dieder; De Muynck, Louis; De Groef, Lies (Frontiers in Aging Neuroscience, 2021)
Although very different in etiology and symptoms, numerous neurodegenerative diseases can be classified as proteinopathies. More so, evidence indicates that the key misfolded proteins at the basis of different neuropathies might share common mechanisms of propagation. As such, the prion-like spreading of protein aggregates through the neural network is subject of intensive research focus and requires adequate models. Here, we made use of the well-defined architecture and large accessibility of the visual system, of which the retinotopic connections represent a simple route of anterograde signaling and an elegant model to investigate transsynaptic, prion-like spreading. In two independent studies, uptake and seeding of alpha-synuclein and tau were examined after intravitreal injection of preformed fibrils. However, extracellular matrix components in the vitreous space and at the vitreoretinal surface appeared to act as a barrier for the entry of both fibrils into the retina. These results show that further experimental refinement is needed to fully realize the potential of the visual system as a model for studying the molecular and cellular mechanisms of anterograde, transsynaptic spreading of prion-like proteins.